What triggers entrepreneurial intention among young generation? the impact of social media - Majid, N.A.; Zainol, F.A.; Afthanorhan, A.; Yusoff, A.S.M.; Rahim, B.H.A.; Ismail, N.A.; Zakaria, R.; Arifin, R.M.; Adnan, W.I.W.; Jaafar, F.W.; Wahab, N.A; Rahman, N.A.A. (2020)
The social media such as Facebook, Instagram, and Tweeter have robustly used in this new era of technology. Despite of the negative impacts imposed by social media related problems like ill health, hackers, and internet addiction, the usage of social media undeniably has implicated positivities in many ways. For instance, the usage of social media in digital business has proved to be effective in attracting the customers to buy the products or services offered. Thus, the usage of social media among young generation is seen as the best way to expose the young people to involve in business. This conceptual paper delibrates some benefits of using social media in digital business as the new way to develop start-up entrepreneur. By reviewing some literature, this paper attempts to explore the significance effect of using social media in triggering entrepreneurial intention among youngsters. The findings indicate that the early involvement in business using social media triggers entrepreneurial intention by intensifying their entrepreneurial knowledge. Ultimately, through the findings of this research, the authors aim to deliver the best way to cultivate entrepreneurial intention among young generation.